STRATEGI PENGEMBANGAN PRODUKSI KERIPIK TALAS (STUDI KASUS PADA USAHA RUMAH TANGGA KHALISTA DI TANAH SIRAH NAGARI KOTO ANAU KECAMATAN LEMBANG JAYA KABUPATEN SOLOK) - Helmayuni, Helmayuni; Firnando, Edi; Putri, Neva Nadia (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Wiraraja, 2022)
Solok Regency is one of the taro producing areas, one of which is in Tanah Sirah Nagari Koto Anau. Farmers in this area have cultivated a lot of taro plants. Taro plants in this area have also been processed into taro chips, as is done by the Khalista household business. This study aims to determine the strategies that can be used for the Khalista taro chips household business in developing its business. The research was conducted using the case study method. The data collected is in the form of primary and secondary data. Sampling of farmers using the Simple Random Sampling technique and samples were taken as many as 31 people or 40% of the 78 people (population). Data analysis used is SWOT analysis. Based on the results of the analysis of the Khalista Talas Chips household business, it is known that the Khalista Talas Chips Home Industry has been established since 2015 and continues to produce until now. This business, which is managed by simple management, continues to grow, producing processed products made from taro plants which are purchased from farmers around the location. The results of the SWOT analysis show that the position of the Khalista Taro Chips home industry business in Lembang Jaya District, Solok Regency is in quadrant I with coordinates (0.84; 1.21), with the strategy formulation being S-O (Aggressive Strategy). This strategy uses internal strengths by taking advantage of external opportunities.